Advances in National Brand and Private Label Marketing : Fourth International Conference, 2017 - Martínez-López, Francisco J.; Gázquez Abad, Juan Carlos; Ailawadi, Kusum L.; Yagüe Guillén, María Jesús (Springer proceedings in business and economics., 2017)
This volume presents the proceedings of the 2017 International Conference on National Brand & Private Label Marketing - a collection of original, rigorous and highly relevant contributions. The 2017 NB & PL marketing conference offers a unique academic forum where researchers present and discuss original and significant contributions on the marketing issues that retailers, store brand managers and national brand managers are now facing. This year, the three-day event covered a wide range of topics from fields as varied as retailing, marketing, general business, psychology, economics and statistics. Further, the conference addressed diverse areas of application, including: purchase-decision models, premium private labels, decisions involved in introducing new products, M-commerce, private label adoption, assortment decisions, private label pricing, brand equity and collaborative relationships. Lastly, a wide variety of theoretical and methodological approaches were also presented, as is reflected in many of the book's chapters.